Toxicity and Molecular Identification of Green Toadfish Lagocephalus lunaris Collected from Kyushu Coast, Japan - Yuji Nagashima; Takuya Matsumoto; Keisuke Kadoyama; Shoichiro Ishizaki; Makoto Terayama (Journal of Toxicology)
Green toadfish Lagocephalus lunaris inhabits tropical and subtropical seas and contains high tetrodotoxin (TTX) levels in the muscle as well as liver and gonad. In 2008 to 2009, food poisoning due to ingesting L. lunais occurred in Western Japan. Five specimens of green toadfish caught in Kyushu coast, Japan, were analyzed for toxicity, toxins, and species identification. All five specimens were toxic by bioassay. Comparing the maximum toxicity in tissues, ovary contained the most toxin (1810 mouse unit [MU]/g), followed by liver (341 MU/g), muscle (135 MU/g), skin (79 MU/g), and intestine (72 MU/g). Liquid chromatography/mass spectrometry analysis revealed that TTX was the major toxin. Nucleotide sequence analysis of the 16S rRNA gene fragment of muscle mitochondrial DNA indicated that partial sequences of PCR products of four specimens were identical with that of L. lunaris. The sequence of one specimen was indistinguishable from that of the brown-backed toadfish Lagocephalus wheeleri, a nontoxic species.